Increase in hepatitis C virus incidence in HIV-1-infected patients followed up since primary infection. Issue 6 (21st August 2006) - Ghosn, J; Deveau, C; Goujard, C; Garrigue, I; Saïchi, N; Galimand, J; Nagy, Z; Rouzioux, C; Meyer, L; Chaix, M-L
Abstract : Background: An increase in the incidence of sexually transmitted infections and hepatitis C virus (HCV) infections in HIV-infected men who have sex with men (MSM) has recently been reported. Objective: To estimate HCV incidence and risk factors among HIV-1-infected patients followed up since primary HIV infection in the French PRIMO Cohort between 1996 and 2005. Patients and methods: All patients with at least 18 months of follow-up were studied. HCV antibody tests were performed on baseline plasma samples and repeated on the latest available sample when negative at baseline. Results: In total, 402 patients with a median follow-up of 36 (range 18–104) months were eligible. HCV seroconversion was observed in 6 patients (4 men and 2 women), corresponding to an HCV incidence rate of 4.3 per 1000 person-years. Incidence rates in men and women were 3.5 and 7.8 per 1000 person-years, respectively. The incidence rate was 1.2 per 1000 person-years before January 2003 and 8.3 per 1000 person-years after January 2003 (p = 0.06). The classic risk factors for HCV infection were found in women (intravenous drug use, and body piercing), whereas the only identified risk factor for HCV acquisition was unsafe sex in the four men. Conclusions: Increase in the incidence of acute HCV infection in recently HIV-infected patients confirms the shift in sexual behaviour in the recent years, especially in HIV-infected MSM. Repeated testing for HCV antibodies should be carried out in HCV-negative HIV-infected patients and specific recommendations about protected sex should be clearly provided.